ANALISIS KUALITAS KINERJA PRAMUWISATA TERHADAP KEPUASAN WISATAWAN JEPANG PADA PARADISE BALI TOUR AND TRAVEL DI BADUNG - Arya Adi Palguna; I Made Sendra; I Nyoman Sudiarta (Jurnal IPTA (Industri Perjalanan Wisata), 2015)
The type of data used are qualitative and quantitative data, while-for the data source is the primary and secondary data. Techniques of data collection is conducted through observation, interviews, and questionnaires. The sampling technique used purposive sampling i.e. applied particular consideration determined by the researcher itself. In another words the researchers have their own criteria toward the Japanese tourists who had ever utilized the services of Paradise Bali Tour and Travel. The result of this study shows that tourists are satisfied by the performance of the Japanese tour guides in Paradise Bali Tour and Travel, with an average rate of suitability is 74.39 percent. Being used Cartesian diagram to analyze the indicators to be a top priority and must be done in accordance with expectations of tourists, such as: guides appearance and neatness and another items and must be used by guide when pick-up the guests, providing clear and accurate information about the condition of destination, and efficiency of time and speedy when pick up the tourists. Indicators are considered important and needed to be maintained its performance are the mastering of foreign languages by guides in order to fluent communication, the courtesy of guides when providing services. Indicators considered less important by tourists but its implementation is quite well done, namely responsiveness guides in providing clear and concise information. Indicator that overestimated by tourist but it have done very well, such as the convenience of tourists when receiving services from the guide during the tour taken place.